2021
DOI: 10.1002/adma.202005155
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy and Combination Therapy Using Anti‐Angiogenic Nanoagents to Fight Cancer

Abstract: Anti‐angiogenic therapy, targeting vascular endothelial cells (ECs) to prevent tumor growth, has been attracting increasing attention in recent years, beginning with bevacizumab (Avastin) through its Phase II/III clinical trials on solid tumors. However, these trials showed only modest clinical efficiency; moreover, anti‐angiogenic therapy may induce acquired resistance to the drugs employed. Combining advanced drug delivery techniques (e.g., nanotechnology) or other therapeutic strategies (e.g., chemotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 222 publications
(227 reference statements)
1
52
0
Order By: Relevance
“…The choice can be monotherapy or combination therapy and depends on several factors like cancer origin, stage, location, and grade. 1 Even though these anticancer therapies can be effective, they have certain disadvantages, like: (a) they can cause pharmacological adverse effects at normal tissues; (b) they lack the ability of center-point targeting deep within tumor mass; (c) they mostly acquire drug resistance and are unable to eradicate the entire cancer cell population in the tumor. 2 Hence, there is an utmost need to develop some innovative therapeutics that should be simple, cost-effective, and could serve as a substitute to conventional treatments to fight cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The choice can be monotherapy or combination therapy and depends on several factors like cancer origin, stage, location, and grade. 1 Even though these anticancer therapies can be effective, they have certain disadvantages, like: (a) they can cause pharmacological adverse effects at normal tissues; (b) they lack the ability of center-point targeting deep within tumor mass; (c) they mostly acquire drug resistance and are unable to eradicate the entire cancer cell population in the tumor. 2 Hence, there is an utmost need to develop some innovative therapeutics that should be simple, cost-effective, and could serve as a substitute to conventional treatments to fight cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence have reported that antiangiogenic agents decrease the immunosuppression by modulating tumor microenvironment (TME) and exhibit synergetic effects when combined with immunotherapies [14]. Previous studies have shown that apatinib exerts its immunomodulatory activity in several tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-angiogenic drugs have also been shown to improve drug delivery efficacy and deeper drug penetration [34][35][36]. In recent reviews [37][38][39], normalization induced by anti-angiogenesis in combination with chemotherapy was introduced as a promising strategy in cancer treatment. Few numerical studies have been performed on drug delivery under the influence of antiangiogenesis-induced vascular normalization.…”
Section: Introductionmentioning
confidence: 99%